Methods of modelling obesity in an animal experiment (analytical literature review) - Prymachenko, V.I. (Medicni Perspektivi, 2025)
The aim of the study was to explore the most effective experimental models of obesity that have been used over many years to study this condition in animals, as well as the models that most closely resemble obesity in humans. The article analyzes the current scientific literature regarding the use of various models to study the most pressing and widespread medical issue of today – obesity. A literature review and analytical analysis were conducted, along with a synthesis of data from scientific literature, which allowed for the examination of various obesity models most commonly used in experimental research by scientists. With the increase in body mass index and the onset of morbid obesity, pathological modifications are observed in all organs and systems of the human body: non-alcoholic fatty liver disease, metabolic syndrome, type 2 diabetes, insulin resistance, dyslipidemia, cardiovascular pathologies, various types of cancer of internal organs, mental disorders, and others. Experimental models of obesity in research animals allow for a deeper understanding of the development and progression of this disorder, which can expand current knowledge about the mechanisms underlying its formation, establish key pathomorphological manifestations, potential complications, and optimize new approaches to the diagnosis and treatment of obesity. However, in contemporary scientific literature, the question of improved and adequate selection of obesity models in animal studies remains open, with results that can be extrapolated to humans. To date, no single animal model can fully represent the entire spectrum of diseases and metabolic disorders associated with obesity in humans. Fatty liver disease represents a spectrum of continuous conditions associated with obesity: type 2 diabetes, insulin resistance, and hyperlipidemia. A significant amount of contemporary scientific literature documents researchers' studies on the progression from simple steatosis to non-alcoholic steatohepatitis, as well as to fibrosis and ultimately to hepatocellular carcinoma. Over the past 5-10 years, researchers have described the most commonly used animal models of fatty liver disease: genetic, chemical, dietary, and others. However, the mechanisms underlying the pathogenesis of obesity and related diseases remain not fully understood, and currently there are few available effective therapeutic approaches in the scientific literature. A large number of different animal models of obesity have been developed and described by researchers to study the pathophysiology of non-alcoholic fatty liver disease. Scientific sources highlight their advantages and disadvantages, as well as provide recommendations for researchers in selecting appropriate animal models.